Single domain antibodies targeting neuraminidase protect against an H5N1 influenza virus challenge - Cardoso, Francisco Miguel (2014)
Influenza virus neuraminidase (NA) is an interesting target of small-molecule antiviral drugs. We isolated a set of H5N1 NAspecific single-domain antibodies (N1-VHHm) and evaluated their in vitro and in vivo antiviral potential. Two of them inhibited the NA activity and in vitro replication of clade 1 and 2 H5N1 viruses. We then generated bivalent derivatives of N1-VHHm by two methods. First, we made N1-VHHb by genetically joining two N1-VHHm moieties with a flexible linker. Second, bivalent N1-VHH-Fc proteins were obtained by genetic fusion of the N1-VHHm moiety with the crystallizable region of mouse IgG2a (Fc). The in vitro antiviral potency against H5N1 of both bivalent N1-VHHb formats was 30- to 240-fold higher than that of their monovalent counterparts, with 50% inhibitory concentrations in the low nanomolar range. Moreover, single-dose prophylactic treatment with bivalent N1-VHHb or N1-VHH-Fc protected BALB/c mice against a lethal challenge with H5N1 virus, including an oseltamivir-resistant H5N1 variant. Surprisingly, an N1-VHH-Fc fusion without in vitro NA-inhibitory or antiviral activity also protected mice against an H5N1 challenge. Virus escape selection experiments indicated that one amino acid residue close to the catalytic site is required for N1-VHHm binding. We conclude that single-domain antibodies directed against influenza virus NA protect against H5N1 virus infection, and when engineered with a conventional Fc domain, they can do so in the absence of detectable NA-inhibitory activity.